Impact properties of thermoplastic composites. Issue 3 (3rd July 2018) - Jogur, Ganesh; Nawaz Khan, Ashraf; Das, Apurba; Mahajan, Puneet; Alagirusamy, R.
Abstract: The excellent properties exhibited by thermoplastic composites at much reduced weight have attracted attention in the development of products in different sectors. Thermoplastic (TP) composites, because of their distinctive properties as well as ease of manufacturing, have emerged as a competitor against the conventional thermoset resin-based composites. Depending on the application, these composites may undergo impact events at various velocities and often fail in many complex modes. Hence, the development of TP composites having high energy-dissipation at (the desired) much-reduced weight has become a challenging task, but it is a problem which may be alleviated through the appropriate selection of materials and fabrication processes. Furthermore, fibre surface modification has been shown to increase fibre-matrix interfacial adhesion, which can lead to improved impact resistance. Textile preforms are helpful in acting as a structural backbone in the composites since they offer a relatively free hand to the composite designer to tailor its properties to suit a specific application. Additionally, hybrid textile composite structures may help in achieving the desired properties at much lower weight. Simulation software can play a significant role in the evaluation of composites without damaging physical samples. Once the simulation result has been validated with actual experimental results, it should be possible to predict the test outcomes for different composites, with different characteristics, at different energy levels without conducting further physical tests. Various numerical models have been developed which have to be incorporated into these software tools for better prediction of the result. In the current issue of Textile Progress, the effects of various materials and test parameters on impact behaviour are critically analyzed. The effect of incorporating high-performance fibres and natural fibres or their hybrid combination on the impact properties of TP composites are also discussed and the essential properties of TP polymers are briefly explained. The effects of fibre and matrix hybridization, environmental factors, various textile preform structures and fibre surface modification treatments on the impact properties of thermoplastic composites are examined in detail. Various numerical models used for impact analysis are discussed and the potential applications of TP composites in automobile, aerospace and medical sectors are highlighted.